2016
DOI: 10.31018/jans.v8i1.780
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of IPM modules for the management of fruit borer and fruit rot diseases in tomato, Lycopersicon esculentum Miller

Abstract: Among, five IPM modules tested against tomato fruit borer and fruit rot on tomato, the IPM module (M3) consisting of use of pheromone traps (@ 12 traps/ha) just after transplanting the tomato crop , Lycopersicon esculentum Miller for monitoring the population of Helicoverpa armigera . followed by three foliar sprays commencing with a mixture of lamba-cyhalothrin 5EC @ 0.8ml/L(0.04%) and Dithane Z-78 (Zineb) @ 2.5g/L (0.25%) after 10 days of appearance of moths in the traps (after 30 days of transplanting) foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…These results are in conformity with those of Usman et al (2012) who used Trichogramma chilonis in field, reported positive results in controlling lepidopterous pests of field crops. Sharma et al (2016) also reported that Trichogramma chilonis are the best bio-control agents for controlling tomato fruit borer after conducting field experiments in tomato crop. Note.…”
Section: Percent Infestation Of Tomato Fruit Borer Treated With Diffementioning
confidence: 98%
See 1 more Smart Citation
“…These results are in conformity with those of Usman et al (2012) who used Trichogramma chilonis in field, reported positive results in controlling lepidopterous pests of field crops. Sharma et al (2016) also reported that Trichogramma chilonis are the best bio-control agents for controlling tomato fruit borer after conducting field experiments in tomato crop. Note.…”
Section: Percent Infestation Of Tomato Fruit Borer Treated With Diffementioning
confidence: 98%
“…Tomato fruit borer Helicoverpa armigera is major threat among the insect pests of tomato causing economical loss (Talekar et al, 2006). Annual crop losses about 5 billion US dollar caused by Helicoverpa armigera alone (Sharma et al, 2016). In Pakistan, 32.37% fruit damage caused by Helicoverpa armigera where fruit loss (54%) was noticed in Peshawar, K.P.K (Usman et al, 2013(Usman et al, ).…”
Section: Introductionmentioning
confidence: 99%